Parametric analysis of a double E-shaped meander line monopole antenna for UHF applications / Nabilah Ripin … [et al.] - Ripin, Nabilah; Sulaiman, Ahmad Asari; Abdul Rashid, Nur Emileen; Hussin, Mohamad Fahmi (Faculty of Electrical Engineering, Universiti Teknologi MARA, Shah Alam, 2017)
A compact double E-shaped meander line monopole antenna for Ultra High Frequency (UHF) applications is proposed. Aim of this study is to design a small and compact printed monopole antenna resonates at UHF band. By adding slots and meander line on the radiating patch, the resonant frequency of the antenna can be reduced with no significant effects on other antenna performances. With overall size of 83.80 mm x 143.74 mm corresponding to 0.123 λ0 x 0.211 λ0, the antenna resonant frequency is reduced from 878 MHz to 440 MHz by inserting the proposed method. Defected ground structure (DGS) is introduced on the partial ground plane to improve the reflection coefficient of the proposed antenna. Parametric analysis are conducted and investigated to provide good antenna performances at targeted frequency band. The proposed antenna exhibits an omnidirectional radiation pattern.